Stereo-Electronic Effects in Tunneling Junctions: Revisiting the Platform. (2016) - Chen, Jiahao; Tevis, Ian; Gathiaka, Symon; Thuo, Martin
Abstract: Stereo-electronic effects in through-bond tunneling in large area molecular junctions have not been widely studied, largely due to a lack of a clear understanding of basic interfacial properties of self-assembled monolayers (SAMs) — the platform on which these junctions are built. Due to a large volume of work in SAMs, it has been largely assumed that their characteristics are well understood, among these, the so-called odd-even effect. This report demonstrates that there is still a lot to be done, or revisited, with regards to SAM formation, characterization, and, potential, if molecular junctions are to emerge as a useful technology. To illustrate this point, the Whitesides-Porter odd-even quandary of the early 90s (in SAM hydrophobicity) is revisited with a new set of data. An overview of recent efforts in our group to improve quality of tunneling junctions is also presented from three key perspective, viz ; i) Surface: optimizing the surface roughness (Au, RMS roughness <2 Å). ii) Interface: studies on the properties of the unbound SAM interface. iii) Molecule: Engineering the stereo-electronic properties to reveal the role of conformational effects on tunneling currents.